Anti-cancer effects of ginsenoside CK on acute myeloid leukemia in vitro and in vivo. Issue 12 (December 2022) - Hou, Yuzhu; Meng, Xiangru; Sun, Kaiju; Zhao, Mingyue; Liu, Xin; Yang, Tongtong; Zhang, Zhe; Su, Rui
Abstract: Objectives: Acute myeloid leukemia (AML) is a malignant disease characterized by clonal proliferation of myeloid cells, and its treatment continues to be a challenge due to high morbidity and mortality. Ginsenoside compound K, a major active metabolite of the protopanaxadiol-type ginsenosides, exhibits biological activities in various cancer cells and animal models. Here, we investigated the role of CK in anticancer potential in AML both in vitro and in vivo. Materials and methods: To investigate the inhibitory effects of CK in AML cells, in vitro experiments, including cell viability assays, colony forming assays, and cell cycle and apoptosis assays were performed. AML animal experiment was established and quantitative analysis of lung tumor growth nodules and spleen weight and H&E staining were carried out to further determine the effects of CK on AML. In addition, the potential key genes induced and influenced by CK during treatment was identification by RNA-seq and qRT-PCR. Results: CK suppressed AML cell activity and induced apoptosis and G1 cell cycle arrest based on the experiment results. Moreover, significantly down-regulated expression genes of BCL2, KIT, DNMT3A, MYC and CSF-1 and up-regulated expression gene of TET2 in CK treatment AML cells were discovered. Conclusion: Our results demonstrated that CK could be used as an anti-AML drug with significant therapeutic efficacy and good biosafety. Abstract : Acute myeloid leukemia; Ginsenoside; CK; Antitumor.